Optimalisasi Gerakan Literasi Sekolah Terhadap Minat Baca Siswa Kelas V SD Negeri 190 Pekanbaru - Nuraini, Salma; Rahmi, Laili (CV. Rayyan Dwi Bharata, 2025)
This study aims to examine how the optimization of the School Literacy Movement influences the reading interest of fifth-grade students at SD Negeri 190 Pekanbaru. This research employed a descriptive qualitative approach with key participants consisting of 30 students from class VB, as well as teachers, librarians, and parents. Data collection techniques included observations of student literacy activities, in-depth interviews with stakeholders, Likert-scale questionnaires to measure students' reading interest, and documentation of school literacy programs. The findings reveal that the implementation of GLS has a positive impact on increasing students' reading interest, particularly in terms of reading intensity, use of free time, and utilization of reading corners. However, the implementation of GLS has not yet been optimal and still requires strengthening in the consistency of activities, diversity of reading materials, and active involvement of teachers and the school environment. Therefore, the optimization of GLS should be carried out continuously to foster a strong literacy culture and improve students' reading interest more evenly.